Psikoedukasi Pada Penyandang Disabilitas: Mempersiapkan Diri Dalam Mengatasi Trauma dan Menghadapi Bencana Alam - Bila, Salsa; Blansiska Bria, Sandra Paula; Matahari, Matahari; Dara Kua, Fransisko Prudensius; Lyke Batoek, Natalie Angel; Gardynia Durry, Ferren Sarita; Pello, Shela Christine (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Indonesia is a country that is highly vulnerable to natural disasters due to its location between active tectonic plates and rings of fire. In disaster conditions, people with disabilities are the most vulnerable group to experience negative impacts, including psychological trauma. This article aims to discuss psychoeducation efforts in dealing with trauma and preparing people with disabilities in Oben Village, Nekamese Sub-district, Kupang Regency in facing natural disasters. Methods: used include lectures, discussions, and assessments related to mental and physical readiness in facing disasters. Results: of this activity showed an increase in participants' understanding of the concept of trauma and strategies for dealing with disasters. Although there was an increase in understanding, there were some challenges, especially related to understanding in the elderly and mentally challenged groups. Conclusion: Therefore, a more intensive approach and follow-up is needed so that understanding is more evenly distributed and can be applied in everyday life.